Analysis of Synchronization Phenomena in Broadband Signals with Nonlinear Excitable Media. (13th October 2009) - Chernihovskyi, Anton; Elger, Christian E.; Lehnertz, Klaus
Abstract : We apply the method of frequency-selective excitation waves in excitable media to characterize synchronization phenomena in interacting complex dynamical systems by measuring coincidence rates of induced excitations. We relax the frequency-selectivity of excitable media and demonstrate two applications of the method to signals with broadband spectra. Findings obtained from analyzing time series of coupled chaotic oscillators as well as electroencephalographic (EEG) recordings from an epilepsy patient indicate that this method can provide an alternative and complementary way to estimate the degree of phase synchronization in noisy signals.